White Paper: Open Digital Health – accelerating transparent and scalable health promotion and treatment. Issue 4 (2nd October 2022) - Kwasnicka, Dominika; Keller, Jan; Perski, Olga; Potthoff, Sebastian; ten Hoor, Gill A.; Ainsworth, Ben; Crutzen, Rik; Dohle, Simone; van Dongen, Anne; Heino, Matti; Henrich, Julia F.; Knox, Liam; et al.
ABSTRACT: In this White Paper, we outline recommendations from the perspective of health psychology and behavioural science, addressing three research gaps: (1) What methods in the health psychology research toolkit can be best used for developing and evaluating digital health tools? (2) What are the most feasible strategies to reuse digital health tools across populations and settings? (3) What are the main advantages and challenges of sharing (openly publishing) data, code, intervention content and design features of digital health tools? We provide actionable suggestions for researchers joining the continuously growing Open Digital Health movement, poised to revolutionise health psychology research and practice in the coming years. This White Paper is positioned in the current context of the COVID-19 pandemic, exploring how digital health tools have rapidly gained popularity in 2020–2022, when world-wide health promotion and treatment efforts rapidly shifted from face-to-face to remote delivery. This statement is written by the Directors of the not-for-profit Open Digital Health initiative (n = 6), Experts attending the European Health Psychology Society Synergy Expert Meeting (n = 17), and the initiative consultant, following a two-day meeting (19–20th August 2021).